Scripturalizing Jewishness through Blackness: Black Jews in France - Mokoko Gampiot, Aurélien (Scripturalization: discourse, formation, power, 2024)
"This book describes the multiple ways in which Black Jews in France practice and claim their Judaism, relate to their fellow Jews, and reconstruct their identities. After fifteen years of fieldwork, Dr. Aurélien Mokoko Gampiot offers an original analysis of their individual and collective itineraries"--